Survey of WO3 thin film structure built on ITO/glass substrates by the Raman and XRD spectroscopies - Ngoc, Le Van; Vinh, Tran Cao; Toai, Le Quang; Thinh, Nguyen Duc; Dat, Huynh Thanh; Tuan, Tran; Phuong, Duong Ai (VNU Journal of Science: Mathematics - Physics, 2009)
Abstract